Tropical saltmarshes are important to juvenile fiddler crabs but not as refuges from large predators or high temperatures. (October 2020) - Reis, Alice; Barros, Francisco
Abstract: Tropical saltmarshes' role as a refuge for macrofauna is poorly known. We tested the hypotheses that: i) there is an increase in abundance of early life-stages of fiddler crabs associated with an increase in vegetation density (thermal and/or predation refuge) and ii) predation are lower within saltmarsh vegetation. The abundance of early life-stages increased with both vegetation density and temperature. Megalopa and juveniles might be adapted or benefit from high temperatures found on tropical saltmarshes and thus do not need protection from it. Predation was higher in saltmarshes than in nearby non-vegetated areas, thus tropical saltmarshes can not be considered a refuge from relatively large predators for juveniles of fiddler crabs. Although not offering refuge against temperature and predation, tropical saltmarshes are important habitats for the recruitment of early life-stages of fiddler crabs. Future studies should consider the evaluation of tropical saltmarsh hydrodynamics in the settlement and permanence of juveniles. Highlights: We tested if tropical saltmarshes are thermal or predation refuge for young crabs. Megalopa and juveniles increased with vegetation density and temperature. Young crabs might be adapted or benefit from high temperatures on tropical saltmarsh. Predation of early life-stages of fiddler crabs was higher within the saltmarsh. Tropical saltmarshes cannot be considered thermal or predation refuge for young crabs.